Boosting the cycle stability and safety of lithium-sulfur batteries via a bilayer, heat-treated electrospun separator. (1st January 2023) - Leng, Xiaolong; Xiao, Wei; Yang, Mingdai; Zeng, Jie; Li, Changping; Chen, Jielin; Arifeen, Waqas Ul; Yoo, Kisoo; Shim, Jaesool; Ko, Tae Jo
Abstract: A multifunctional lithium–sulfur–battery separator, the heat-treated PAN/CB/VOOH-PAN/PVDF(HFP) (HPCVPP), was synthesized using a single-step electrospinning technique and heat treatment. The HPCVPP separator has two layers for its functions. (i) The PAN/CB/VOOH, close to the Li–S battery cathode, acts as the conductive blocking layer. The conductive blocking layer provides a site for the electrochemical reaction of LIPS species. In addition, the polar VOOH of this layer can adsorb and catalyze LIPS species, slowing down the 'shuttle effect'. The batteries using the HPCVPP separator exhibited a close-to-theoretical-maximum capacity of 1391 mAh/g at 0.1C and maintained a high capacity (644 mAh/g) even after 500 cycles at 2C. (ii) The second layer is PAN/PVDF(HFP). In particular, the PAN/PVDF(HFP) helps achieve good thermal stability of the HPCVPP separator. The HPCVPP contour can still be maintained at 250 °C, which can ensure the high-temperature safety of the battery. Moreover, the PVDF(HFP) was heat-treated and generated a crosslinked structure between the nanofibers, enhancing the mechanical strength of the separator from 10.6 to 20.8 MPa, which can further improve battery safety. The HPCVPP separator exhibited outstanding performance, including high level of porosity (70.7%), high electrolyte uptake (510.4%), good ionic conductivity (2.81 mS/cm), and excellent electrochemical performance.